2021
DOI: 10.1037/fam0000835
|View full text |Cite
|
Sign up to set email alerts
|

Within-person associations between romantic involvement and mental health among sexual and gender minorities assigned female-at-birth.

Abstract: Sexual and gender minorities assigned female at birth (SGM-AFAB) experience significant mental health disparities, making it important to identify protective factors against psychological and substance use problems in this population. We examined whether romantic relationship involvement, a well-established protective factor for mental health in heterosexual adults, is protective for SGM-AFAB young people. Using five waves of data from 488 racially diverse SGM-AFAB (ages 16-31 years at baseline), we assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Our results are largely in line with the more narrowly focused existing studies of mean differences in personality, social relationships, and health (Anderssen et al, 2020;Batz & Tay, 2018;Bogaert et al, 2018;Cusack et al, 2012;Ehlke et al, 2020;Eres et al, 2021;Ferlatte et al, 2020;Hendricks & Testa, 2012;Hyde & Mezulis, 2020;[anonymized], 2022;Meyer, 2003;Plöderl & Tremblay, 2015;Valentine & Shipherd, 2018;Whitton et al, 2021). Few studies dissect the variance, the distribution, and overlap or the differences in correlation outside the context of narrowly defined moderation models.…”
Section: Discussionsupporting
confidence: 87%
“…Our results are largely in line with the more narrowly focused existing studies of mean differences in personality, social relationships, and health (Anderssen et al, 2020;Batz & Tay, 2018;Bogaert et al, 2018;Cusack et al, 2012;Ehlke et al, 2020;Eres et al, 2021;Ferlatte et al, 2020;Hendricks & Testa, 2012;Hyde & Mezulis, 2020;[anonymized], 2022;Meyer, 2003;Plöderl & Tremblay, 2015;Valentine & Shipherd, 2018;Whitton et al, 2021). Few studies dissect the variance, the distribution, and overlap or the differences in correlation outside the context of narrowly defined moderation models.…”
Section: Discussionsupporting
confidence: 87%
“…It is likely that a number of developmental factors unique to sexual minority youth contribute to their perception that they had fewer relationship skills, compared with their heterosexual peers, such as having fewer examples of sexual minority romantic relationships in the media and fewer available dating partners (Bond, 2014;Diamond, 2003a;Gowen & Winges-Yanez, 2014). While romantic relationship involvement appears protective for sexual minority youths' mental health (Whitton et al, 2018;Whitton et al, 2021), a robust literature has shown that relationship quality also contributes to health benefits (Robles et al, 2014;Slatcher & Selcuk, 2017). Further, research has also demonstrated that sexual minority youth are at particularly high risk of experiencing dating violence as adolescents (Freedner et al, 2002;Whitton et al, 2019aWhitton et al, , 2019b and intimate partner violence as adults (Edwards et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This null finding may have been due to limited variability and positive skew in the AUDIT scores in this sample; perhaps the large minority of nondrinkers, including many under the age of 21, limited our ability to detect associations with relationship quality. In addition, all participants in this sample were currently involved in a romantic relationship, which is associated with less problematic drinking in SGM-AFAB (Whitton et al, 2020(Whitton et al, , 2021, potentially further limiting variability and power to detect effects. Alternately, it is possible that high relationship quality does not reduce drinking during times of high stress, in the way that it reduces use of other substances (Leonard & Homish, 2008).…”
mentioning
confidence: 99%